Photovoice study on the well-being of family caregivers with older care recipient users and non-users of long-term care services (LTCS) in Singapore - Lim, Rebecca Zhao Chu (Nanyang Technological University, 2024)
Singapore is a rapidly ageing society faced with an increasing life expectancy of older adults. More often than not, these older adults are living longer yet many of them are suffering from chronic illnesses. This can take a toll not just on the Singapore healthcare system but also on their family caregivers. To care for these older adults, family members have to take on such caregiving roles, sometimes unexpectedly. Caregivers play a crucial in providing quality care for their older care recipients. The quality of care provided for the care recipient is influenced by the well-being of their caregivers. Given the limited studies conducted on long-term care service (LTCS) utilisation in Singapore, this present study aims to examine the effects of LTCS and non-LTCS usage on the well-being of caregivers. As such, qualitative research was conducted using the photovoice method along with a focus group discussion to understand each caregiver’s experience. The following themes of how LTCS use or non-use affects caregiver’s well-being were uncovered: (a) LTCS non-use improves physical health and social relationships but increases stress for caregivers; (b) LTCS use supplements informal caregiving by family caregivers and (c) Psychosocial aspects of caregiving. Understanding the facilitators and inhibitors of well-being from care recipients’ use of LTCS provides greater insights into ways of improving the well-being of caregivers.